Development of a GERANA E-Module Using Book Creator for Elementary Dance Education - Fatimah Nurussyifa Clever Bright; Deasylina da Ary (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop, determine the feasibility, and examine the effectiveness of the GERANA E-Module assisted by the Book Creator application in dance education. The study employed a Research and Development (R&D) method using the ADDIE model. The research subjects consisted of material experts, media experts, teachers, and fourth-grade elementary school students. Data were collected through interviews, observations, questionnaires, tests, and documentation and were analyzed using quantitative descriptive techniques. The development process resulted in the GERANA E-Module, which features text, images, and interactive videos. The novelty of the module lies in the integration of natural phenomenon-based movement concepts into elementary dance education. The validation results showed scores of 91.4% from material experts and 96% from media experts, both of which were categorized as highly feasible. The effectiveness of the module was evaluated using pretest and posttest data analyzed through normality tests, t-tests, and N-gain analysis. The t-test results showed a significance value of Sig. (2-tailed) < 0.001, indicating a significant difference between the pretest and posttest scores, while the N-gain score of 0.5733 was categorized as moderate. In conclusion, the GERANA E-Module is highly feasible and effective in improving students’ motor skills in dance learning, particularly in the topic of understanding the environment through dance among fourth-grade elementary school students.